SUATU KRITERIA STABILISASI SISTEM DESKRIPTOR LINIER KONTINU REGULAR - Sari, Yulian (UNIVERSITAS RIAU KEPULAUAN, BATAM, INDONESIA, 2014)
Abstract.The regular descriptor linear time-invariant system, or shorthandly this system is denoted by are used in many applications, especially in mathematical modeling for engineering, biology, and economics. In this paper, the characterization of stabilization of this systems. Feedback control for some and is used for stabilizing the system such that the closed-loop system is stable. Some examples is given to illustrate this characteristic. Keywords: regular descriptor linear time-invariant system, stabilization, stabilizable.